PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK ETOS KERJA KRISTEN PADA GENERASI MUDA DI ERA POSTMODERNISME - Hesthy Widjiawasi Marri; Kristiani Andiso; Ole' Rotto'; Meriyani Yusrin; Anggita Yulia Gallungan (EDUCATIONAL JOURNAL : General and Specific Research, 2025)
This study aims to analyze the role of Christian Religious Education in shaping a Christian work ethic among young people in the postmodern era. This era is characterized by relativism of truth, individualism, and rapid technological change, which often pose challenges for young people in finding a firm moral and spiritual foundation. The Christian work ethic, which includes values such as honesty, responsibility, discipline, and work as worship, serves as a critical foundation for addressing these challenges. Using a qualitative approach through literature review methods, this study finds that CRE plays a strategic role in instilling Christian work ethic values through the teaching of God’s Word, discipleship, and character formation. Scriptures such as Colossians 3:23 (“Whatever you do, work at it with all your heart, as working for the Lord, not for human masters”) provide a theological foundation that encourages young people to view work as a divine calling. CRE also contributes to shaping young people who can navigate the cultural challenges of postmodernism by making Christian faith the foundation of their lives. The findings show that collaboration between the church, family, and Christian schools in implementing CRE can strengthen the formation of a Christian work ethic among young people. Thus, CRE not only serves as a means of spiritual education but also as a tool for cultural transformation, preparing young people to become agents of change who glorify God in the midst of the postmodern world.